Nuclear abnormalities in cells from nasal epithelium: a promising assay to evaluate DNA damage related to air pollution in infants - Michelle Mergener; Cláudia R. Rhoden; Sérgio L. Amantéa (Brazilian Society of Pediatrics, 2014)
Objectives: This study intends to provide a quick, easy, and inexpensive way to assess nuclear abnormalities such as micronuclei and bud frequencies; binucleated, karyorrhectic, karyolytic, pycnotic, and condensed chromatin cells in nasal scrapings of infants, which are particularly important for conducting genotoxic studies related to the inhaled atmosphere in pediatric populations. Methods: Nasal swab samples were collected from 40 infants under 12 months of age using a small cytobrush. 2,000 cells from each infant sample were analyzed and classified according to the frequency of nuclear abnormalities. Results: Rates of nuclear abnormalities found agree with values reported in other studies of neonates and children. This study found 0.13% of cells with micronuclei; 1.20% karyorrhexis; 0.03% pyknosis; 10.85% karyolysis; 1.11% condensed chromatin; 0.54 binucleated cells; and 0.02% nuclear bud. Differences were not observed between genders or environmental passive smoking, nor was any age correlation found. Conclusion: The assay proposed here is suitable for assessing the frequency of nuclear abnormalities from nasal cells in infants.